Mozambique. Export perespectives - Joanna Sitz-Kuleszo (Contemporary Economy, 2014)
Destroyed by wars, military and internal conflicts economy of Republic of Mozambique since more than a decade is constantly growing. This 36th biggest country in the world became the object of interest for investment and trade for many developed economies, mostly from Asia. Nowadays investments in Mozambique are focused mostly on rich carbon and gas sources that has been discovered during last decade. Poland is not important trade partner for Mozambique, however could intensify exchange in upcoming years as, if the development will continue, Republic of Mozambique would need for its economy Polish export specialties.